Analisis Persepsi Wajib Pajak Pelaku UMKM Terhadap Penerapan Peraturan Menteri Keuangan No. 44 Tahun 2020 - Fadli, Ach. Marzuki; Afifudin, Afifudin; Hariri, Hariri (Universitas Islam Malang, 2023)
This study aims to analyze and provide an overview of the perceptions of UMKM taxpayers regarding Minister of Finance Regulation No 44 of 2020 in terms of Tax Understanding, Tax Rates, Tax Sanctions, Tax Ease and Tax Dissemination. This research was conducted on UMKM assisted by DISKOPINDAG Malang City using a qualitative method approach. The results of the study show that many UMKM actors assisted by DISKOPINDAG do not take advantage of the government-borne final income tax incentive (DTP). The perceptions of UMKM actors regarding understanding of taxation, tax rates, tax sanctions, tax convenience and tax socialization are quite good. The majority of UMKM are only aware of the existence of a tax incentive policy, but many of the UMKM do not really understand how to use PMK incentives No. 44 of 2020. Judging from the current facts, the benefits are small, the lack of socialization and the majority of UMKM are still low in tax literacy and low understanding of the use of information technology are the causes of UMKM lack of understanding of this policy.Keywords: Perception of taxpayers, understanding of taxation, tax rates, tax sanctions, tax ease, tax dissemination, PMK no 44.